Investigation on recovery stress and stability of hot-drawn Ni47Ti44Nb9 SMA. (1st March 2023) - Pan, Shengshan; Yan, Dong; Zhang, Xue; Zou, Cunyu; Chen, Yuanmeng; Hui, Huaxing; Chen, Sile; Andrawes, Bassem
Abstract: Ni47 Ti44 Nb9 shape memory alloys (SMAs) have been studied as a seismic confinement reinforcement for bridge pier columns. The confinement method relies on the force generated in SMA because of the thermally activated recovery stress. Most of the work done on NiTiNb focused on characterizing the behavior of annealed wires, and almost no work was done on the application of hot-drawn wires despite their cost-effectiveness. Aiming at exploring the usability of hot-drawn NiTiNb SMA as pier reinforcement, this paper focuses on investigating the specific thermomechanical characteristics of the hot-drawn wires including pretension characteristics, thermal activation, and partial recovery of recoverable strain. The recovery stress stability of constraint SMA under cyclic loads both in room temperature and low temperature are also studied. The states of recovery stress and its stability are mainly evaluated by three tests: pretension test, thermal activation test, and cyclic loading test. A total of 54 specimens were tested in the experiment. The results indicate that hot-drawn NiTiNb SMA could obtain sufficient recovery stress (about 480 MPa) when deformed at room temperature which has not been found in annealed SMA. Small partial recovery shape (48% recoverable strain loss in this paper) would not notably reduce recovery stress. Moreover, the stability of recovery stress under cyclic loading and low temperature could satisfy the demands of pier column reinforcement for practical use.